1983
DOI: 10.1039/f19837901701
|View full text |Cite
|
Sign up to set email alerts
|

Wall effects in du Noüy ring tensiometry. Theory and experiment

Abstract: A rigorous theory of wall effects in du Nouy ring tensiometry is developed which is no more difficult to compute than the infinite-wall theory of Huh and Mason. The predictions of the theory are compared with experimental measurements on wetting and non-wetting walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, the ratio of the ring radius to the dish radius could be calculated and was found to be 4.8/0.954 = 5.03. The size of the crystallizing dishes was initially chosen based on this ratio to avoid wall effects (14). • To prevent any effects due to the floor of the container, at least 100-mL samples were used in the crystallizing dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the ratio of the ring radius to the dish radius could be calculated and was found to be 4.8/0.954 = 5.03. The size of the crystallizing dishes was initially chosen based on this ratio to avoid wall effects (14). • To prevent any effects due to the floor of the container, at least 100-mL samples were used in the crystallizing dishes.…”
Section: Methodsmentioning
confidence: 99%
“…In previous AFM surface tension measurements in air the liquid drops were often very large or flat pools of liquid where edge effects were neglected. , A detailed analysis on edge effects for the geometry of a drop below the capillary length has not been performed. However, earlier theoretical and experimental studies of edge effects in the du Noüy ring method and other force balance methods suggest that the ratio of the distance to the drop edge to probe diameter must be large to neglect edge effects. , The analysis performed by Furlong et al showed in a dimensionless analysis that the ratio of the probe object to the distance from the edge must be large (on the order of 5 for the du Noüy ring). This analysis is derived using interfacial continuum mechanics principles, which are expected to apply to the microdrops used in this study as well.…”
Section: Resultsmentioning
confidence: 99%